A Formação inicial do professor alfabetizador: experiências autobiográficas no PIBID - SILVA, Anderson André Alves da (2022)
This article presents the trajectory of the formation of a graduate student in the Pedagogy course, especially with regard to participation as a fellow in the Institutional Program for Teaching Initiation Scholarships (PIBID), specifically in the subproject Interdisciplinary Practices of Literacy and Literacy in Elementary Education developed at the Municipal School of Elementary Education Júlia Quadros Peinado, located in Bragança municipality, Rio Caeté region, state of Pará. The object of study is the literacy and literacy experience lived in the formative course of initiation to teaching at PIBID. The general objective is to analyze the contributions of the PIBID subproject to the initial training of the literacy teacher. The article sought to answer the following problem questions: What lessons did PIBID provide about the literacy and literacy process in the initial cycle of elementary school? What theoretical and practical knowledge about literacy and literacy has been provided by PIBID? What was it possible to learn about the practice of literacy and literacy with literacy teachers at the PIBID field school? What didactic-pedagogical experiments in literacy and literacy were offered to the groups of early years of elementary school in the rural school? The research follows a qualitative approach, anchored in the methodology of autobiographical research, the data collection was carried out in the daily coexistence with school agents, during the eighteen months of the project's duration. The theoretical basis of the work was built from the bibliographic studies carried out during the theoretical-methodological training meetings proposed by the subproject (PIBID). The results point to the fact that literacy does not have a relevant concern in view of the daily pedagogical practices of literacy teachers and literacy is still very much centered on mechanized reading and writing activities.